Phenolic resin-based copper-clad plate filled with boron nitride micro powder and preparation method of phenolic resin-based copper-clad plate
By introducing modified boron nitride micropowder and hyperbranched flame retardant toughening agent into the phenolic resin-based copper clad plate, combined with phenolic epoxy resin and diluent, the problem of insufficient flame retardancy and mechanical strength of the phenolic resin-based copper clad plate is solved. Boron nitride micropowder filled copper clad plate with excellent flame retardant and impact properties was prepared.
Patent Information
- Application Number
- CN202411605859.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The existing phenolic resin-based copper clad plates cannot meet the high flame retardancy requirements and have low mechanical strength, which limits its application.
By introducing modified boron nitride micropowder and hyperbranched flame retardant toughening agent, combined with phenolic epoxy resin and diluent, a resin glue solution with flame retardant and toughening is prepared, and the glass fiber cloth impregnation and hot pressing composite technology is used to combine with phenolic epoxy resin and diluent. A phenolic resin-based copper clad plate filled with boron nitride micropowder was prepared.
It significantly improves the flame retardant performance and mechanical strength of copper clad plate, improves the toughness and processing properties of resin, and meets the needs of high flame retardant and high mechanical strength.
Smart Images

Figure BDA0005129545360000071
Abstract
Description
Technical Field
[0001] The invention relates to the field of copper-clad laminates, and specifically discloses a phenolic resin-based copper-clad laminate filled with boron nitride micropowder and a preparation method thereof. Background Art
[0002] Phenolic resin is low-cost and has good performance. It is widely used in the fields of automobiles, electronics, transportation, aerospace, etc. Linear phenolic resin is commonly used to prepare copper clad laminates. Linear phenolic resin has better heat resistance, water resistance, corrosion resistance, mechanical properties and electrical insulation. Linear phenolic resin is used in combination with epoxy resin to obtain materials with good thermal conductivity, electrical insulation, dielectric and other properties.
[0003] However, copper clad laminates have high requirements for flame retardancy, and unmodified phenolic resins cannot meet the flame retardancy requirements of copper clad laminates. In addition, phenolic resins are brittle and have low mechanical strength, which limits their application. Therefore, it is of great significance to study a phenolic resin-based copper clad laminate that has both flame retardancy and mechanical strength. Summary of the invention
[0004] The object of the present invention is to provide a phenolic resin-based copper-clad laminate filled with boron nitride micropowder and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride micropowder comprises the following steps: S1: taking phenolic resin, modified boron nitride micropowder, phenolic epoxy resin, epoxy resin, diluent, flame retardant toughening agent, and imidazole, mixing them evenly, and emulsifying them at high speed shearing to obtain a resin glue solution;
[0007] S2: impregnating glass fiber cloth in resin glue, pulling it out, and drying it to obtain a prepreg; stacking 5 to 10 prepregs to obtain a substrate, pasting copper foil on both sides of the substrate, hot pressing and compounding, and obtaining a phenolic resin-based copper clad laminate.
[0008] Preferably, the resin adhesive comprises the following raw materials, calculated by mass: 15-20 parts of phenolic resin, 6-8 parts of modified boron nitride powder, 0.5-1 parts of phenolic epoxy resin, 1-2 parts of epoxy resin, 0.1-0.2 parts of diluent, 2-4 parts of flame retardant toughening agent, and 0.01-0.03 parts of imidazole.
[0009] Preferably, the epoxy resin is bisphenol A epoxy resin, the phenolic resin is linear phenolic resin, and the diluent is dodecyl-tetradecyl glycidyl ether.
[0010] Preferably, the preparation of the flame retardant toughening agent comprises the following steps: taking a hyperbranched modifier, DOPO, ethanol, water, and N,N-dimethylformamide, heating and stirring at 60-70° C. for 4-6 hours, cooling, filtering, washing, and vacuum drying to obtain the flame retardant toughening agent.
[0011] Preferably, the flame retardant toughening agent comprises the following raw materials, calculated by weight: 20 to 30 parts of hyperbranched modifier, 5 to 10 parts of DOPO, 100 to 200 parts of ethanol, 50 to 100 parts of water, and 50 to 100 parts of N,N-dimethylformamide.
[0012] Preferably, the preparation of the hyperbranched modifier comprises the following steps: S1: taking 2,4-diaminophenol, p-hydroxybenzaldehyde and ethanol, stirring evenly, stirring at 60-70° C. for 3-4 hours, cooling to room temperature, filtering, washing and vacuum drying to obtain a modifier;
[0013] S2: 3-(tert-butyldimethylsilyloxy)glutaric anhydride, modifier, p-toluenesulfonic acid, water and N,N-dimethylformamide are mixed, heated at 95-100° C. for 6-8 hours, and dried by vacuum distillation to obtain a hyperbranched modifier.
[0014] Preferably, the modifier comprises the following raw materials, calculated by mass: 20 to 30 parts of 2,4-diaminophenol, 15 to 25 parts of p-hydroxybenzaldehyde, and 300 to 400 parts of ethanol; the hyperbranched modifier comprises the following raw materials, calculated by mass: 20 to 30 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 10 to 15 parts of modifier, 0.3 to 0.8 parts of p-toluenesulfonic acid, 40 to 60 parts of water, and 40 to 60 parts of N,N-dimethylformamide.
[0015] Preferably, the preparation of the modified boron nitride micropowder comprises the following steps: taking hexagonal boron nitride nanosheet powder, urea and water, ball milling at room temperature, washing and drying to obtain modified boron nitride micropowder.
[0016] Preferably, the modified boron nitride powder comprises the following raw materials, calculated by weight: 0.5 to 1 part of hexagonal boron nitride nanosheet powder, 30 to 40 parts of urea, and 10 to 15 parts of water.
[0017] Preferably, the amount of the phenolic epoxy resin added is 50-60% of the mass of the epoxy resin, and the amount of the diluent added is 8-15% of the mass of the epoxy resin.
[0018] Preferably, the preparation of the prepreg comprises the following steps: impregnating the glass fiber cloth with resin glue, pulling it out, and drying it to obtain a prepreg, wherein the amount of glue applied is 150-200 g / m 2 .
[0019] Preferably, the preparation of the prepreg comprises the following steps: impregnating the glass fiber cloth with resin glue, pulling it out, and drying it to obtain a prepreg, with the glue amount being 160g / m 2 .
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: (1) preparing a flame retardant toughening agent: preparing a modifier with 2,4-diaminophenol and p-hydroxybenzaldehyde, and then preparing a modifier containing a hyperbranched structure by reacting 3-(tert-butyldimethylsilyloxy)glutaric anhydride with the modifier, and introducing silicon element with good flame retardancy and heat resistance; the hyperbranched structure can introduce a large amount of free volume, so that the chain segments can respond quickly under the action of load, thereby consuming energy and improving toughness. The structure is also conducive to uniform dispersion in the resin matrix, and the flame retardant effect is better while also improving the toughness of the resin matrix and improving the brittleness of the phenolic resin; at the same time, the hyperbranched structure improves the fluidity of the resin matrix, reduces the viscosity, and makes it easier to process; then, the carbon-nitrogen double bond structure in the hyperbranched modifier is reacted with DOPO to introduce phosphorus element, thereby obtaining a hyperbranched flame retardant toughening agent containing silicon, nitrogen and phosphorus at the same time, further improving the flame retardant effect;
[0021] (2) Preparation of modified boron nitride powder containing hydroxyl groups, while improving dispersibility, its hydroxyl structure can assist curing, increase the degree of crosslinking, improve mechanical strength and thermal stability, but excessive crosslinking will lead to a decrease in performance, so the amount added needs to be controlled;
[0022] (3) The adhesive contains phenolic epoxy resin, bisphenol A epoxy resin, and diluent dodecyl glycidyl ether. The phenolic epoxy resin has better thermal stability, but has a higher viscosity, so the amount added should not be too high. At the same time, the fluidity is adjusted by introducing the diluent and the aforementioned hyperbranched flame retardant toughening agent to obtain an adhesive with excellent processing properties, flame retardant properties, and mechanical properties. DETAILED DESCRIPTION
[0023] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0024] The following parts are by mass unless otherwise specified;
[0025] Example 1: S1: Take 25 parts of 2,4-diaminophenol, 20 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4 hours, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0026] S2: 25 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 12 parts of a modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95° C. for 8 h, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0027] S3: Take 25 parts of hyperbranched modifier, 8 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0028] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0029] S5: Take 20 parts of linear phenolic resin, 8 parts of modified boron nitride powder, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 3 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed of 1000 rpm for 2 hours to obtain a resin glue;
[0030] S6: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0031] Example 2: S1: Take 30 parts of 2,4-diaminophenol, 25 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4 hours, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0032] S2: 30 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 15 parts of a modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95° C. for 8 h, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0033] S3: Take 30 parts of hyperbranched modifier, 10 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0034] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0035] S5: Take 20 parts of linear phenolic resin, 8 parts of modified boron nitride powder, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 4 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed of 1000 rpm for 2 hours to obtain a resin glue;
[0036] S6: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0037] Example 3: S1: Take 20 parts of 2,4-diaminophenol, 15 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4 hours, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0038] S2: 20 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 10 parts of modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95° C. for 8 h, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0039] S3: Take 20 parts of hyperbranched modifier, 5 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0040] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0041] S5: Take 15 parts of linear phenolic resin, 6 parts of modified boron nitride powder, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 2 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed of 1000 rpm for 2 hours to obtain a resin glue;
[0042] S6: Dip the glass fiber cloth in the resin glue, pull it out, and dry it at 190℃ for 3min to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, stick copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210℃, a hot-pressing pressure of 4Mpa, and a pressing time of 120min to obtain a phenolic resin-based copper-clad laminate.
[0043] Comparative Example 1 (using itaconic anhydride instead of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, and the remaining steps are consistent with Example 1): S1: Take 25 parts of 2,4-diaminophenol, 20 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70° C. for 4 hours, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0044] S2: 25 parts of itaconic anhydride, 12 parts of modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95°C for 8 hours, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0045] S3: Take 25 parts of hyperbranched modifier, 8 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0046] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0047] S5: Take 20 parts of linear phenolic resin, 8 parts of modified boron nitride powder, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 3 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed of 1000 rpm for 2 hours to obtain a resin glue;
[0048] S6: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0049] Comparative Example 2 (changing the amount of raw materials added to the resin glue, and the other method steps are consistent with Example 1): S1: Take 25 parts of 2,4-diaminophenol, 20 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4h, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0050] S2: 25 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 12 parts of a modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95° C. for 8 h, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0051] S3: Take 25 parts of hyperbranched modifier, 8 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0052] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0053] S5: Take 20 parts of linear phenolic resin, 8 parts of modified boron nitride powder, 2 parts of phenolic epoxy resin, 1 part of epoxy resin, 0.1 parts of dodecyl glycidyl ether, 1 part of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed of 1000 rpm for 2 hours to obtain a resin glue;
[0054] S6: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0055] Comparative Example 3 (the preparation method of the flame retardant toughening agent is changed, and the other method steps are consistent with Example 1): S1: Take 25 parts of 2,4-diaminophenol, 20 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4h, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0056] S2: Take 17 parts of modifier, 8 parts of hyperbranched modifier, and 8 parts of DOPO, mix them evenly, and obtain a flame retardant toughening agent;
[0057] S3: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0058] S4: Take 20 parts of linear phenolic resin, 8 parts of 3-(tert-butyldimethylsilyloxy) glutaric anhydride, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 3 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed shear rate of 1000 rpm for 2 hours to obtain a resin glue;
[0059] S5: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0060] Comparative Example 4 (changing the amount of modified boron nitride powder added, the other method steps are consistent with Example 1): S1: Take 25 parts of 2,4-diaminophenol, 20 parts of p-hydroxybenzaldehyde, and 400 parts of ethanol, stir evenly, stir at 70°C for 4h, cool to room temperature, filter, wash, and vacuum dry to obtain a modifier;
[0061] S2: 25 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 12 parts of a modifier, 0.6 parts of p-toluenesulfonic acid, 50 parts of water, and 50 parts of N,N-dimethylformamide were mixed, heated at 95° C. for 8 h, and dried by vacuum distillation to obtain a hyperbranched modifier;
[0062] S3: Take 25 parts of hyperbranched modifier, 8 parts of DOPO, 200 parts of ethanol, 80 parts of water, and 80 parts of N,N-dimethylformamide, heat and stir at 70°C for 5 hours, cool, filter, wash, and vacuum dry to obtain a flame retardant toughening agent;
[0063] S4: Take 1 part of hexagonal boron nitride nanosheet powder, 35 parts of urea, and 15 parts of water, ball mill at room temperature, each ball milling for 30 minutes, with an interval of 10 minutes, a total of ball milling for 2 hours, wash, and dry to obtain modified boron nitride micropowder;
[0064] S5: Take 20 parts of linear phenolic resin, 10 parts of modified boron nitride powder, 1 part of phenolic epoxy resin, 2 parts of epoxy resin, 0.2 parts of dodecyl glycidyl ether, 3 parts of flame retardant toughening agent, and 0.02 parts of imidazole, mix them evenly, and emulsify them at a high speed shear rate of 1000 rpm for 2 hours to obtain a resin glue;
[0065] S6: Immerse the glass fiber cloth in the resin glue, pull it out, and dry it at 190°C for 3 minutes to obtain a semi-cured sheet; stack 6 semi-cured sheets to obtain a substrate, paste copper foil on both sides of the substrate, and hot-press and laminate them at a hot-pressing temperature of 210°C, a hot-pressing pressure of 4Mpa, and a pressing time of 120 minutes to obtain a phenolic resin-based copper-clad laminate.
[0066] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); bisphenol A epoxy resin (E44, epoxy equivalent 210-240 g / eq, Nanjing Bermuda Biotechnology Co., Ltd.); imidazole (CAS: 288-32-4); 2,4-diaminophenol (CAS: 95-86-3); p-hydroxybenzaldehyde (CAS: 123-08-0); 3-(tert-butyldimethylsilyloxy)glutaric anhydride (CAS: 91424- 40-7); p-toluenesulfonic acid (CAS: 104-15-4); N,N-dimethylformamide (CAS: 68-12-2); DOPO (9,10-dihydro-9-oxa-10-phosphane, CAS: 35948-25-5); hexagonal boron nitride nanosheet powder (Article No.: 52352, Xi'an Qiyue Biotechnology Co., Ltd.); urea (CAS: 57-13-6); linear phenolic resin (Grade No. 8013, Shandong Jinan Shengquan Group Co., Ltd.); phenolic epoxy resin (F51, Chengfeng); dodecyl glycidyl ether (CAS: 2461-18-9).
[0067] Experiment: Take the phenolic resin-based copper clad laminates prepared in Examples 1 to 3 and Comparative Examples 1 to 4, (1) refer to the standard ASTM D2863-2008, test the limiting oxygen index LOI, the sample size is 130 mm × 6.5 mm × 3.2 mm; (2) refer to GB / T 1043.1-2008, and perform impact test on a ZBC1400-A pendulum impact tester, the sample size is 100 mm × 12 × 6 mm; specific data are shown in the table below;
[0068]
[0069] Conclusion: In Comparative Example 1, itaconic anhydride was used instead of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, and silicon was not introduced, resulting in a decrease in flame retardant performance; in Comparative Example 2, the amount of raw materials added to the resin glue was changed, the amount of phenolic epoxy resin added was increased, and the amount of epoxy resin, diluent, and flame retardant toughening agent added was reduced. The performance of the obtained product was not as good as that of the embodiment. The possible reasons are: when the viscosity is high, the dispersibility of the modified boron nitride powder in the system will be affected, resulting in a decrease in flame retardant effect. High viscosity may also lead to stress concentration during curing and reduce impact strength. ; In Comparative Example 3, the modifier, 3-(tert-butyldimethylsilyloxy)glutaric anhydride, and DOPO are added separately, that is, there is no hyperbranched structure, and the flame retardant ability and impact strength are significantly reduced; In Comparative Example 4, the amount of modified boron nitride micropowder added is increased. On the one hand, excessive addition of filler will lead to uneven dispersion problems. On the other hand, the addition of modified boron nitride micropowder may lead to excessive cross-linking, thereby affecting the flame retardant and impact properties; In summary, the phenolic resin-based copper clad laminate filled with boron nitride micropowder prepared by the present invention has excellent flame retardant properties and impact strength.
[0070] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride micropowder, characterized in that: The following steps are involved: S1: preparing a flame retardant toughening agent: taking 2,4-diaminophenol, p-hydroxybenzaldehyde and ethanol, stirring and reacting, cooling, filtering, washing and drying to obtain a modifier; Mix 3-(tert-butyldimethylsilyloxy)glutaric anhydride, a modifier, p-toluenesulfonic acid, water, and N,N-dimethylformamide, heat to react, and dry to obtain a hyperbranched modifier; Take a hyperbranched modifier, DOPO, ethanol, water, and N,N-dimethylformamide, heat and stir, cool, filter, wash, and dry to obtain a flame retardant toughening agent; S2: Preparation of phenolic resin-based copper-clad laminate: phenolic resin, modified boron nitride powder, phenolic epoxy resin, epoxy resin, diluent, flame retardant toughening agent, imidazole, mix well, and emulsify at high speed shear to obtain resin glue; The glass fiber cloth is immersed in the resin glue, pulled out, and dried to obtain a semi-cured sheet; the semi-cured sheets are stacked to obtain a substrate, copper foil is attached to both sides of the substrate, and hot-pressed to obtain a phenolic resin-based copper-clad laminate.
2. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride micropowder according to claim 1, characterized in that: The resin glue comprises the following raw materials, calculated by weight: 15 to 20 parts of phenolic resin, 6 to 8 parts of modified boron nitride powder, 0.5 to 1 part of phenolic epoxy resin, 1 to 2 parts of epoxy resin, 0.1 to 0.2 parts of diluent, 2 to 4 parts of flame retardant toughening agent, and 0.01 to 0.03 parts of imidazole.
3. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 1, characterized in that: The flame retardant toughening agent comprises the following raw materials, calculated by weight: 20 to 30 parts of hyperbranched modifier, 5 to 10 parts of DOPO, 100 to 200 parts of ethanol, 50 to 100 parts of water, and 50 to 100 parts of N,N-dimethylformamide.
4. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride micropowder according to claim 1, characterized in that: The modifier comprises the following raw materials, calculated by weight: 20 to 30 parts of 2,4-diaminophenol, 15 to 25 parts of p-hydroxybenzaldehyde, and 300 to 400 parts of ethanol; the hyperbranched modifier comprises the following raw materials, calculated by weight: 20 to 30 parts of 3-(tert-butyldimethylsilyloxy)glutaric anhydride, 10 to 15 parts of the modifier, 0.3 to 0.8 parts of p-toluenesulfonic acid, 40 to 60 parts of water, and 40 to 60 parts of N,N-dimethylformamide.
5. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 1, characterized in that: The preparation of the modified boron nitride micropowder comprises the following steps: Take hexagonal boron nitride nanosheet powder, urea and water, ball-mill at room temperature, wash and dry to obtain modified boron nitride micropowder.
6. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 5, characterized in that: The modified boron nitride micropowder comprises the following raw materials, calculated by weight: 0.5 to 1 part of hexagonal boron nitride nanosheet powder, 30 to 40 parts of urea, and 10 to 15 parts of water.
7. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 2, characterized in that: The addition amount of the phenolic epoxy resin is 50-60% of the mass of the epoxy resin, and the addition amount of the diluent is 8-15% of the mass of the epoxy resin.
8. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 1, characterized in that: The conditions for the hot pressing composite are: the hot pressing temperature is 200-210° C., the hot pressing pressure is 3-4 MPa, and the pressing time is 100-150 min.
9. The method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to claim 1, characterized in that: The preparation of the prepreg comprises the following steps: impregnating the glass fiber cloth with resin glue, pulling it out, and drying it to obtain the prepreg, wherein the glue amount is 150-200 g / m 2 .
10. A phenolic resin-based copper-clad laminate prepared according to the method for preparing a phenolic resin-based copper-clad laminate filled with boron nitride powder according to any one of claims 1 to 9.
Citation Information
Patent Citations
Phosphorus-nitrogen containing halogen-free flame-retardant hyperbranched epoxy resin and preparation method thereof
CN106832219A
Edge hydroxylation modification method for hexagonal layered boron nitride
CN108559131A
Hyperbranched silicon-phosphorus synergistic flame retardant modified epoxy resin and preparation method thereof
CN110591288A
Phenolic resin-based copper-clad plate and preparation method thereof
CN116080210A
Ceramic toughened epoxy resin for halogen-free copper-clad plate and preparation method thereof
CN116285229A